Expanding the genotypic and phenotypic spectrum of severe serine biosynthesis disorders. Issue 9 (15th July 2020) - Abdelfattah, Fatima; Kariminejad, Ariana; Kahlert, Anne‐Karin; Morrison, Patrick J.; Gumus, Evren; Mathews, Katherine D.; Darbro, Benjamin W.; Amor, David J.; Walsh, Maie; Sznajer, Yves; Weiß, Luisa; Weidensee, Sabine; et al.
Abstract: Serine biosynthesis disorders comprise a spectrum of very rare autosomal recessive inborn errors of metabolism with wide phenotypic variability. Neu–Laxova syndrome represents the most severe expression and is characterized by multiple congenital anomalies and pre‐ or perinatal lethality. Here, we present the mutation spectrum and a detailed phenotypic analysis in 15 unrelated families with severe types of serine biosynthesis disorders. We identified likely disease‐causing variants in the PHGDH and PSAT1 genes, several of which have not been reported previously. Phenotype analysis and a comprehensive review of the literature corroborates the evidence that serine biosynthesis disorders represent a continuum with varying degrees of phenotypic expression and suggest that even gradual differences at the severe end of the spectrum may be correlated with particular genotypes. We postulate that the individual residual enzyme activity of mutant proteins is the major determinant of the phenotypic variability, but further functional studies are needed to explore effects at the enzyme protein level. Abstract : Dimeric PSAT1 structure with the bound pyridoxal 5′‐phosphate shown in stick presentation. In one subunit, variants associated with lethal and nonlethal phenotypes are highlighted by red and orange balls, respectively